Penentuan Lokasi Fasilitas Postponement Pada Rantai Pasok Ordinary Portland Cement - Fauzan Romadlon; Hari Kurniawan (Jurnal Ilmiah Teknik Industri, 2018)
This research deals with the problem of postponement facility siting for distributing OPC cements produced by PT. Semen Jawa. In order to obtain the optimum value of the site location, centre of gravity (CoG) method is applied. From calculation, a location in Jatiwarna, Bekasi with longitutede and latitude of -6.30687 dan 106.9311, respectively, is selected. I addition, for the reason of efficiency, it is suggested in this paper the PT. Semen Jawa should share a location of SCG batching plant in Kampung Rambutan as a postponement facility.